Double UV polymerisation with variable temperature-controllable selective reflection of polymer-stabilised liquid crystal (PSLC) composites. Issue 10 (8th August 2016) - Xiao, Ling; Cao, Hui; Sun, Jian; Wang, Huihui; Wang, Dong; Yang, Zhou; He, Wanli; Xiao, Jiumei; Ding, Hangjun; Yang, Huai
ABSTRACT: In this study, a method of preparing wide-band reflection cholesteric liquid crystals (CLCs) films by UV-radical polymerisation in combination with UV-cationic polymerisation is proposed. Because the helical twisting power (HTP) of the chiral dopant decreases with increasing temperature and the polymerisation rate of UV-initiated free radical polymerisation is faster than UV-initiated cationic polymerisation, by adjusting the temperature, broadband reflective films with non-uniform pitch distribution are obtained. The fractured surface of the polymer network of the broadband reflective films is observed by scanning electron microscopy (SEM), which reveals the presence of non-uniform pitch distribution. In addition, the influences of monomer concentration, UV light intensity and UV curing time on the consequent non-uniform pitch distribution have been studied. GRAPHICAL ABSTRACT: